Analisis Pengaruh Faktor Makroekonomi Dan NPF Terhadap Profitabilitas Bank Syari'ah Di Indonesia - Annisa Della Vernon; Norma Rosyidah (DPPM Universitas Pelita Bangsa, 2026)
One of the supporting factors of monetary policy that can support the profitability of Islamic banks in Indonesia is inflation, interest rates, net performing finanace (NPF). Profitability utilizes Return on Assets (ROA) as the main indicator of bank financial performance. Inflation reflects the general level of price increases that can affect people's purchasing power, while interest rates reflect the cost of borrowing that impacts economic activity. NPF is utilized to indicate the quality of Islamic banking and the credit risk it faces. Inflation has a significant positive impact on the profitability of Islamic banks, which reflects that inflation can improve bank performance through an increase in people's purchasing power and an increase in operating costs. Interest rates have a negative influence on the profitability of Islamic banks because as sharia-based financial institutions, Islamic banks are in principle not directly affected by interest rates, suggesting an indirect relationship with adjustments to the level of Islamic financing. Meanwhile, NPF shows a significant positive effect on Profitability, indicating that increased financing risk reduces the bank's ability to generate profits.